Antifouling mechanism of natural product-based coatings investigated by digital holographic microscopy. (10th September 2021) - Pan, Jiansen; Peng, Qingmei; Zhang, Guoliang; Xie, Qingyi; Gong, Xiangjun; Qian, Pei-Yuan; Ma, Chunfeng; Zhang, Guangzhao
Graphical abstract: Highlights: A novel 3D tracking technique-DHM is used to clarify the antifouling mechanism. Bio-sourced poly(lactic acid)-based polyurethane has been used as the polymer binder. The used eco-friendly antifoulant (butenolide) is from the sea and for the sea. Butenolide can drive the bacteria away from the coating surface but without killing them. Abstract: Using natural product-based antifouling coatings has proven to be an effective strategy to combat biofouling. However, their antifouling mechanisms are still unclear. In this study, the antifouling mechanism of natural product-based coatings consisting of bio-sourced poly(lactic acid)-based polyurethane and eco-friendly antifoulant (butenolide) derived from marine bacteria was revealed by observing 3D bacterial motions utilizing a 3D tracking technique-digital holographic microscopy (DHM). As butenolide content increases, the density of planktonic marine bacteria ( Pseudomonas sp.) near the surface decreases and thus leads to a reduced adhesion, indicating that butenolide elicits the adaptive response of Pseudomonas sp. to escape from the surface. Meanwhile, among these remained cells, an increased percentage is found to undergo subdiffusive motions compared with the case of smaller dose of butenolide. Further experiments show that butenolide can accelerate their swimming velocity and reduce flick frequency. Antibacterial assay confirms that butenolide-based coating shows high efficacy of antifouling performance against Pseudomonas sp. but without killing them like 4, 5-dichloro-2- n -octyl-4-isothiazolin-3-one (DCOIT).